1995
DOI: 10.1164/ajrccm.152.1.7599844
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced hydrogen peroxide production in intact pulmonary circulation of rat.

Abstract: Although the importance of free oxygen radical has been reported in acute lung injury, the direct evidence in vivo model was lacking. We report a new method, which for the first time allows direct detection of hydrogen peroxide in the intact rat pulmonary microcirculation. We used the computer image-analyzing system and 2',7'-dichlorofluorescin diacetate for the marker of hydrogen peroxide production in vivo. A rat sepsis model was produced by continuous infusion of endotoxin for 30, 60, and 120 min. Hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Also, recent evidence has indicated that superoxide anion production and PMN phagocytic activity are impaired in the presence of LPS [9]. In addition, there has been no direct, convincing evidence for the production of active oxygen radicals from the LPS-treated lungs, although Minamiya et al [13] showed that hydrogen peroxide was produced in the rat pulmonary microcirculation in vivo using fluorescent dye and a computer image analysis system. However, they could not prove that the increased production of active oxygen radicals induced the lung injury since indices of vascular permeability, the wet/dry ratio, and Evans blue dye method remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent evidence has indicated that superoxide anion production and PMN phagocytic activity are impaired in the presence of LPS [9]. In addition, there has been no direct, convincing evidence for the production of active oxygen radicals from the LPS-treated lungs, although Minamiya et al [13] showed that hydrogen peroxide was produced in the rat pulmonary microcirculation in vivo using fluorescent dye and a computer image analysis system. However, they could not prove that the increased production of active oxygen radicals induced the lung injury since indices of vascular permeability, the wet/dry ratio, and Evans blue dye method remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…LUNG DISEASES, SUCH AS ASTHMA (10), chronic obstructive pulmonary disease (12), endotoxin shock (33), and vascular microembolism (50), or inhalation of oxidant irritants, such as toxic smoke (35), cigarette smoke (35), and ozone (45), may cause increased pulmonary production of reactive oxygen species from endogenous and/or exogenous sources. The major reactive oxygen species are the superoxide anion radical, hydrogen peroxide (H 2 O 2 ), and the hydroxyl radical (⅐ OH) (5).…”
mentioning
confidence: 99%
“…Transition metal ions have been suggested to play a role in endotoxin-induced lipid peroxidation [18]. Endotoxin is capable of enhancing the generation of reactive oxygen species [6,7,34], which in turn may release iron from its protein complex. Therefore, increased reactive oxygen species generation resulting from endotoxin treatment may promote iron release from ferritin or other protein complexes.…”
Section: Discussionmentioning
confidence: 99%